Peningkatan Pemahaman Tentang Berpikir Positif Melalui Metode Problem Based Learning Berbantuan Role Playing - Fara, Elly Leo (Jurnal Pembelajaran Prospektif, 2017)
Counseling plays an important role to be given to the student in person or group, so that they reach maturity and attitude and the ability to think positive in everything that happens in this life. To enhance students' understanding of positive thinking ability, the researchers seek to improve service by using the method of Problem Based Learning (PBL) aided Role Playing. PBL is a learning model that uses matter as a first step in collecting and integrating new knowledge. This method is aided by the method of role playing or playing a role. At BK services to enhance the understanding of positive thinking students are given problems / events going on around them. Furthermore, students solve and take the positive things in the problem that eventually integrate knowledge about the importance of positive thinking. Further events / issues that serve students in role play activities / role playing.Strategi Problem Based Learning aided Role Playing very interesting for students to understand the ability to think positively.